Beyond histological remission: the role of mucosal calprotectin as a potential predictor of outcomes in ulcerative colitis. - Guirgis, M; Wendt, E; Wang, L; Walsh, A; Burger, D; Bryant, R; Kent, A; Adamson, R; Brain, O; Travis, S; Keshav, S (Oxford University Press, 2016)
Background Histological remission and low faecal calprotectin are positive prognostic factors in ulcerative colitis (UC). Intramucosal calprotectin (iMC), which can be readily determined by immunohistochemistry, has not so far been evaluated as a predictor of outcome in UC. Aims To investigate the relationship between iMC and clinical, endoscopic and histological measures of remission in UC, and the independent prognostic value of iMC. Method Ambulant patients with UC were recruited for a study comparing clinical activity indices. Sigmoidoscopy and biopsy were performed at the index visit. Clinical, endoscopic and histological activity was scored and iMC semi-quantitatively measured using immunohistochemistry for the S100A8/9 heterodimer on colonic biopsies, scored as the mean number of positive cells in five high power fields (HPF). At the end of follow up (six years), data on steroid use, hospitalisation, and colectomy (‘adverse outcomes’) were collected. Results iMC was determined in 83 patients and 20 controls, and correlated with clinical, endoscopic and histological activity (r=0.51, 0.65, 0.53 p>0.001, respectively). iMC was lowest (median 2.4, IQR: 5.2-5 p<0.001) in patients with concordance between clinical, endoscopic and histological remission. Median iMC>5/HPF was associated with adverse outcome (HR 3.36 CI 1.58-7.15, p<0.001). Only 53%, 33%, and 25% of patients in histological remission with iMC >5cells/HPF avoided an adverse outcome after 1, 3 and 6 years respectively. Conclusion iMC was lowest in patients with concordant clinical, endoscopic and histological remission. Median iMC >5/HPF was associated with adverse outcomes despite histological remission. Therefore iMC is a potentially useful independent marker of activity.